Haar wavelet based algorithm for solution of second order electromagnetic problems in time and space domains. Issue 3 (11th February 2020) - Kumar, Arun; Hashmi, Mohammad S.; Ansari, Abdul Q.; Arzykulov, Sultangali
Abstract: In this paper, a novel wavelet algorithm has been proposed for solving second order electromagnetic problems both in time and space domains. The algorithm has been used to solve four different problems, i.e. the transmission line problem, the problems associated with electromagnetic waves travelling in different media, the problem related to uniform plane wave in lossy dielectric and problem associated with the telegrapher's equation. The comparison between the results obtained using the proposed approach and the conventional numerical techniques demonstrate that the proposed technique exhibits better time complexity. In essence, the proposed algorithm possesses complexity of order O ( n ) whereas the conventional technique possesses complexity order of O ( n 2 ) . Furthermore, the memory requirement of the proposed algorithm is significantly lower when compared to the conventional technique.